Global food security and supply - Martindale, Wayne, 1965- (Chichester, West Sussex, UK : Wiley Blackwell, 2015)
'With the global population projected to reach 9 billion by the year 2050, the need for nations to secure food supplies for their populations has never been more pressing. Finding better supply chain solutions is an essential part of achieving a secure and sustainable diet for a rapidly increasing population. We are now in a position, through methods including life cycle assessment (LCA), carbon footprinting and other tools, to accurately measure and assess our use - or misuse - of natural resources, including food. The impact of new technologies and management systems can therefore improve efficiencies and find new ways to reduce waste.Global Food Security and Supply provides robust, succinct information for people who want to understand how the global food system works. The book demonstrates the specific tools available for understanding how food supply works, addresses the challenges facing a secure and safe global food supply, and helps readers to appreciate how these challenges might be overcome.This book is a concise and accessible text that focuses on recent data and findings from a range of international collaborations and studies. The author provides both a snapshot of global food supply and security today, and a projection of where these issues may lead us in the future. This book will therefore be of particular interest to food policy leaders, commercial managers in the food industry, and researchers and students seeking a better understanding of a rapidly evolving topic'--
Includes bibliographical references and index.
Keywords: Food supply; Food security